2019
DOI: 10.1016/j.bbrc.2018.12.107
|View full text |Cite
|
Sign up to set email alerts
|

IFT20 is required for the maintenance of cartilaginous matrix in condylar cartilage

Abstract: Condylar cartilage is a joint cartilage essential for smooth jaw movement. The importance of ciliary proteins in condylar cartilage development has been reported. However, little is known about how ciliary proteins control the homeostasis of condylar cartilage. Here we show that intraflagellar transport 20 (IFT20), a ciliary protein, is required for the maintenance of cartilaginous matrix in condylar cartilage. Utilizing NG2-CreER mice expressed in condylar cartilage, we deleted Ift20 by tamoxifen treatment at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…Because the mice with neural crest-specific deletion of IFT20 died shortly after birth due to difficulties in feeding and breathing, another mouse line with chondrocyte-specific deletion of IFT20 at juvenile-to-adult stages was obtained (Kitami et al, 2018). In accordance with the previous studies, the maturation process of condylar cartilage was disrupted, owing to the lower amount of collagen type X and reduced proliferation.…”
Section: Ift Subunits and Cellular Secretionsupporting
confidence: 57%
“…Because the mice with neural crest-specific deletion of IFT20 died shortly after birth due to difficulties in feeding and breathing, another mouse line with chondrocyte-specific deletion of IFT20 at juvenile-to-adult stages was obtained (Kitami et al, 2018). In accordance with the previous studies, the maturation process of condylar cartilage was disrupted, owing to the lower amount of collagen type X and reduced proliferation.…”
Section: Ift Subunits and Cellular Secretionsupporting
confidence: 57%
“…These observations possibly rule out GMAP210-related defects in the collagen secretion phenotype, despite this mutation also resulting in impaired glycosylation and secretion of non-collagenous matrix molecules, namely perlecan. Kitami et al found that IFT20 knockout in adult mouse cartilage leads to loss of cilia, Hh signalling defects, and, in contrast to developmental IFT20 deletion, Golgi morphological changes due to altered input and output of cargo [63]. These morphological changes and decreased secretion are also observed in GMAP210 mutant patient-derived cells, indicating that these defects may be related more to changes in global secretory load, than specific, IFT20-mediated, trafficking from the Golgi [64].…”
Section: Ift20 Links the Golgi To The Ciliummentioning
confidence: 99%
“…G, The potential mechanism of IFT20 is to regulate the Golgi size and Hedgehog signalling transduction to control the maintenance of the condylar cartilage. Reprinted with permission from Ref . Copyright 2019 Elsevier…”
Section: Primary Cilia and Cartilage Developmentmentioning
confidence: 99%